Burning International Bridges, Fuelling Global Discontent: The United States and Rejection of the Kyoto Protocol - Joyner, Christopher C (Victoria University of Wellington Law Review, 2002)
This address was presented on 31 October 2001 by Professor Christopher C. Joyner as the 2001 Quentin Quentin-Baxter Memorial Lecture at the Victoria University of Wellington School of Law. Professor Joyner came to New Zealand as a Visiting Canterbury Fellow with the School of Law and Gateway Antarctica at the University of Canterbury from September through December 2001. This paper tackles the controversy surrounding the rejection of the Kyoto Protocol by the United States of America. The paper's particular focus is the international effect of rejection. An updated epilogue discusses the result of the conclusion of the United Nation's Climate Change Convention, and the reaction of the United States.